Liquid-liquid flows and separation - Simmons, Mark John Harry (1998)
The transport and separation of oil and water is a vital process to the oil and chemical industries. Fluids exiting from oil wells usually consist of gas, oil and water and these three phases need to be transported and separated before they can be processed further.